2023
DOI: 10.3390/diagnostics13030527
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Study of Kato-Katz and Helmintex Methods for Diagnosis of Schistosomiasis Mansoni in a Moderate Endemicity Area in Sergipe, Northeastern Brazil

Abstract: Schistosomiasis is a neglected tropical disease (NTD) caused by blood flukes from the genus Schistosoma. Brazil hosts the main endemic area in the Americas, where Schistosoma mansoni is the only species causing the disease. Kato-Katz (KK) thick smear is the WHO recommended screening test for populational studies, but there is growing evidence for the sensitivity limitations associated with KK, especially in areas with low parasite loads. Helmintex (HTX) is another highly sensitive egg-detection method, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The original research articles were on point-of-care CCA (two articles), CRISPR (one article), multidiagnostic microscope (one article), and Helminthex (one article). 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 These articles might have added some value to our comparisons based on CCA, CAA, and Helminthex. One research study was done in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original research articles were on point-of-care CCA (two articles), CRISPR (one article), multidiagnostic microscope (one article), and Helminthex (one article). 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 These articles might have added some value to our comparisons based on CCA, CAA, and Helminthex. One research study was done in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
“… 153 Since we finalised our analyses, we checked for new studies and found that nine that met our inclusion criteria were published between Jan 1 to April 23, 2023, of which two were reviews 154 , 155 and seven original research articles. 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 The two reviews were a meta-analysis evaluating the accuracy of antigen, antibody, and molecular tests for S mansoni and S haematobium only that did not use Bayesian latent class models, and a scoping review on proteins for antibody-based tests. The original research articles were on point-of-care CCA (two articles), CRISPR (one article), multidiagnostic microscope (one article), and Helminthex (one article).…”
Section: Discussionmentioning
confidence: 99%
“…For urogenital schistosomiasis, the urine filtration technique is the standard diagnostic method and for intestinal schistosomiasis, the Kato Katz technique is the standard diagnostic method (6)(7)(8). In addition to high specificity (7,9), both techniques have minimal operational costs (the test kits are inexpensive), low complexity and they are relatively easy to perform in resource-limited field settings (6,8,9). Moreover, prepared Kato Katz slides can be stored for months at room temperature for later microscopic examination.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the techniques is limited by the host infection intensity, daily variation of schistosome egg excretion and uneven distribution of eggs within stool specimens (11). Additionally, both methods are unable to diagnose recent infections (for instance, in cases where worms have not yet started to produce eggs) or single worm/sex infections and the Kato Katz technique is unable to analyse watery stool specimens (9). The lack of sensitivity especially in low endemic areas and after successful control interventions lead to underestimation of true schistosomiasis prevalence in such settings (710).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation